Prediction of Leakage Current and Depletion Voltage in Silicon Detectors Under Extraterrestrial Radiation Conditions - Grummer, A.; Hoeferkamp, M. R.; Seidel, S. (Frontiers in Physics, 2021)
Silicon detection is a mature technology for registering the passage of charged particles. At the same time it continues to evolve toward increasing radiation tolerance as well as precision and adaptability. For these reasons it is likely to remain a critical element of detection systems associated with extra-terrestrial exploration. Silicon sensor leakage current and depletion voltage depend upon the integrated fluence received by the sensor, and upon its thermal history during and after the irradiation process. For minimal assumptions on shielding and hence on particle energy spectrum, and using published data on Martian ground temperature, we predict the leakage current density and depletion voltage, as a function of time, of silicon sensors deployed continuously on the Mars surface for a duration of up to 28 Earth-years, for several sensor geometries and a worst-case temperature scenario.